Effect of Exercises Using Rubber Bands On the Development of Special Strength In Young Volleyball Players - Gassim, Nassif; Muhammed, Firas (Journal of Physical Education, 2018)
Effect of Exercises Using Rubber Bands On the Development of Special Strength In Young Volleyball Players The research aimed at identifying the effect of exercises using rubber bands on the development of explosive strength and power speed in volleyball. The researchers used the experimental group on (8) players from the national center for gifted in volleyball. Pretested were conducted followed by the exercises using rubber bands in (24) training sessions. The data was collected and treated using proper statistical operations to conclude that the training program using rubber bands have a positive effect on developing arms and legs explosive strength and strength defined by speed. Finally the researchers recommended using modern methods and styles in training for developing performance level as well as the necessity of benefiting from training methods due to their effects in developing special strength level.